Highly efficient energy transfer from a carbonyl carotenoid to chlorophyll a in the main light harvesting complex of Chromera velia - Durchan, Milan; Keşan, Gürkan; Slouf, Václav; Fuciman, Marcel; Staleva, Hristina; Tichý, Josef; Litvín, Radek; Bína, David; Vácha, František; Polívka, Tomáš (Biochimica et biophysica acta, 2014)
We report on energy transfer pathways in the main light-harvesting complex of photosynthetic relative of apicomplexan parasites, Chromera velia. This complex, denoted CLH, belongs to the family of FCP proteins and contains chlorophyll (Chl) a, violaxanthin, and the so far unidentified carbonyl carotenoid related to isofucoxanthin. The overall carotenoid-to-Chl-a energy transfer exhibits efficiency over 90% which is the largest among the FCP-like proteins studied so far. Three spectroscopically different isofucoxanthin-like molecules were identified in CLH, each having slightly different energy transfer efficiency that increases from isofucoxanthin-like molecules absorbing in the blue part of the spectrum to those absorbing in the reddest part of spectrum. Part of the energy transfer from carotenoids proceeds via the ultrafast S2 channel of both the violaxanthin and isofucoxanthin-like carotenoid, but major energy transfer pathway proceeds via the S1/ICT state of the isofucoxanthin-like carotenoid. Two S1/ICT-mediated channels characterized by time constants of ~0.5 and ~4ps were found. For the isofucoxanthin-like carotenoid excited at 480nm the slower channel dominates, while those excited at 540nm employs predominantly the fast 0.5ps channel. Comparing these data with the excited-state properties of the isofucoxanthin-like carotenoid in solution we conclude that, contrary to other members of the FCP family employing carbonyl carotenoids, CLH complex suppresses the charge transfer character of the S1/ICT state of the isofucoxanthin-like carotenoid to achieve the high carotenoid-to-Chl-a energy transfer efficiency.
Keywords: Energy Transfer; Alveolata; Chlorophyll; chlorofyl; Light-Harvesting Protein Complexes; Spectrometry, Fluorescence; Apicomplexa; Energy transfer; světlosběrné proteinové komplexy; Carbonyl carotenoids; Carotenoids; fluorescenční spektrometrie; Chlorophyll A; FCP; Light-harvesting; chlorofyl a; přenos energie; karotenoidy